PRINSIP DASAR HUKUM POLITIK ISLAM DALAM PERSPEKTIF AL-QURAN - Mutiara Fahmi (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2017)
The principle is a norm or value that is agreed universally. The basic principles of the electoral law is needed in order to run the state administration system in Islam which is very dynamic and moves quickly.This study attempted to formulate some basic principles of the laws of political Islam from the perspective of the Quran which is the law of political Islam (fiqh siyasah) is a law that continues to grow rapidly and dynamically, This development requires a knowledge of the basic principles of what defined the scholars in the field siyasah so that the legal development of political Islam does not out of the track and norms that have been agreed upon, both in terms of theory and application.According to Islam, the operating mechanism of the government and constitutional refers to Shari'ah principles which is derived from the Quran and Hadits. The principles of the Islamic state in any of these are basic principles that refer to the clear and unequivocal texts of Shari'ah, and there are additional principles that is conclution and included to fiqh siyasah or Islamic constitutional law.Legal principles of political Islam that has been described by experts on political Islam in various references are very varied, but the study to the principles siyasah and administration of the state in the Qur'an can be formulated seven basic principles of the electoral law of Islam. namely: 1). The principle of sovereignty; 2). The principle of justice; 3). The principle of syura and consensus'; 4). The principle of equality; 5). The principle of the rights and obligations of the state and the people; 6). The principle of amar ma’ruf nahi munkar. Abstrak: Kajian ini bertujuan merumuskan prinsip dasar hukum politik Islam menurut perspektif Al-Quran mengingat hukum politik Islam (fiqh siyasah) adalah hukum yang terus berkembang dengan cepat dan dinamis, Perkembangan ini memerlukan pengetahuan tentang prinsip-prinsip dasar apa yang dirumuskan para ulama dalam bidang siyasah sehingga perkembangan hukum politik Islam tidak lari dari rel dan norma standar yang telah disepakati. Menurut Islam, mekanisme operasional pemerintahan dan ketatanegaran mengacu pada prinsip-prinsip syari’ah yang bersumber dari Al-Quran dan Hadis. Prinsip-prinsip negara dalam Islam tersebut ada yang berupa prinsip-prinsip dasar yang mengacu pada teks-teks syari’ah yang jelas dan tegas, dan ada pula prinsip-prinsip tambahan yang merupakan kesimpulan dan termasuk ke dalam fiqh siyasah atau Hukum ketatanegaraan dalam Islam. Prinsip-prinsip hukum politik Islam yang telah diuraikan oleh para pakar politik Islam dalam berbagai referensi sangat variatif, dalam kajian ini prinsip-prinsip siyasah dan penyelenggaraan negara dalam Alquran dapat diformulasikan tujuh prinsip dasar hukum politik Islam. yaitu : 1). Prinsip kedaulatan; 2). Prinsip keadilan; 3). Prinsip musyawarah dan Ijma’; 4). Prinsip persamaan; 5). Prinsip hak dan kewajiban negara dan rakyat; 6). Prinsip amar ma’ruf nahi munkar. Kata kunci: Prinsip Dasar, Politik Islam